The Use of Loose Parts Media To Improve Alphabet Recognition At TK IT Nurul Fikri Padangsidimpuan - Efrinayanti Efrinayanti (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2026)
This study aims to determine the alphabet recognition skills of children in Group B, including correctly naming, pointing to, and differentiating letter shapes. Children were able to distinguish between the letters b and d, n and h, w and m, m and n, and f and t using Loose parts Media. Loose parts Media utilizes loose materials derived from natural materials such as seeds, stones, twigs, shells, sand, soil, etc., and manufactured materials such as garlands, beads, lifeboats, Lego, buttons, etc., which can enhance children's creativity and encourage active participation in learning and exploring their surroundings. The study used the Classroom Action Research (CAR) method, implemented in two cycles. The study population was all 12 children in Group B. Data collection techniques included observation, checklists, and documentation. Tests were used to obtain data and to assess alphabet recognition skills through play, finding letters, making letter shapes, and grouping letters based on their shapes. The research results revealed that the use of Loose parts Media improved the alphabet recognition skills of children in Group B, with 66.25% achieving success in Cycle I and 88.75% achieving success in Cycle II, categorized as "good." Therefore, the use of Loose parts Media is effective in improving alphabet recognition in children in Group B.